Molecular detection and quantification of Plasmodium vivax DNA in blood pellet and plasma samples from patients in Senegal - Sambe, Babacar Souleymane; Diagne, Aissatou; Diatta, Hélène Ataume Mawounge; Gaba, Folly Mawulolo; Sarr, Ibrahima; Diatta, Arona Sabène; Diaw, Serigne Ousmane Mbacké; Sané, Rokhaya; Diouf, Babacar; Vigan-Womas, Inès; Mbengue, Babacar; Niang, Makhtar (Frontiers in Parasitology, 2023)
Background The first discovery of Plasmodium vivax infections in Senegal used archived patients’ sera in place of blood pellet, the preferred specimen for the molecular diagnosis of Plasmodium species. The present study assessed the reliability of detecting P. vivax DNA in plasma in comparison to blood pellet from the same patient’s samples. Methods A total of 616 blood samples obtained from febrile patients living in Kolda (2015 and 2020), Tambacounda (2017 and 2020), and Kedougou (2020) regions in Senegal, were first screened for Plasmodium species composition by 18S ssrRNA-based nested PCR. Paired blood pellets and plasma samples were selected from a subset of 50 P. vivax-positive patients matched by age and sex with 50 P. vivax-negative patients, and subjected to a cytochrome b-based qPCR to compare the detection and quantification of P. vivax genomic DNA between the two specimen types. Results and discussion The study reports 1.8% and 14.77% of single and mixed P. vivax infections in the study population, and a high concordance (84%) between the qPCR detection of P. vivax genomic DNA from paired blood pellets and plasma samples. Importantly, all P. vivax negative samples from the blood pellets were also confirmed plasma-negative, and parasitaemia in blood pellets was higher compared to plasma samples. The results support investigations of P. vivax infections in archived sera or plasma collections with a high degree of confidence to generate additional data on the neglected P. vivax malaria, and ultimately guide strategies to control the disease.